KEARIFAN LOKAL MASYARAKAT DESA TUNGGUL BOYOK DALAM PENGELOLAAN MADU ALAM DI KECAMATAN BONTI KABUPATEN SANGGAU - kael, Mi; Hardiansyah, Gusti; kandar, Is (Universitas Tanjungpura, 2015)
Abstrack Local wisdom society is a reflection of culture in maintaining and managing the environment, forests and natural resources. The study aims to reveal and bring back the Local wisdom that is believed to society long ago until today. The study used descriptive qualitative survey and interview techniques, the selection of informants is the snowball sampling technique. The number of informants were taken in this study was 35 informants. The results reveal that villagers Tunggul Boyok wisdom in the management of natural honey are forms of Local wisdom as a ban on felling trees and honey bees nest farming ban around the tree where the bees nest. Such prohibition is assessed from the customs is very crucial because Tapang tree is a known human incarnation Dayang Sebunai. According to public confidence if Kempassia sp felled tree as well as treason. Ceremony / customs before and after harvesting as : Tree Care and cleaning around the tree Tapang, ahead of Muar Manyi tradition '(the bees for honey harvesting), Early evening already assembled group (after sunset) and held the division of the working group). Society in assigning work group again there are some parts such as: group tebaok maker (torches to repel bees), group jatak maker (ladder to climb into the tree), a group that prepares food and Muar Manyi '. Keyword : Community, local wisdom, natural honey.